A flexible and lightweight user‐demand DRM system for multimedia contents over multiple portable device platforms. (17th February 2017) - Wu, Eric Hsiaokuang; Chuang, Shumin; Shih, Chen‐Yen; Hsueh, Hao‐Che; Huang, Shih‐Syuan; Huang, Hsiao‐Ping
Summary: With the rapid development of technology, digital multimedia has been widely utilized. Access of multimedia contents has become a daily routine. Although multimedia brings ease and convenience for content sharing, it also makes piracy more feasible. For example, it is easy to upload a copyrighted video to YouTube without the owners' permission. Authors and merchants are very much in need of protecting their intellectual property and commercial profits. Digital right management (DRM) systems are provided to fulfill this desire. DRM is a collection of techniques used to control access to copyrighted materials. Because current enterprise DRM solutions are not allowed for customized modification, they cannot fit in our considered scenario perfectly. As a result, we propose a secure DRM system with a design based on user demands, where a consumer can access contents only on authenticated devices until the authorization expires. Our DRM scheme involves a series of robust cryptosystems including AES, SHA‐256, and RSA. Applications as DRM agents are implemented on Windows, Mac OS, Android, and iOS platforms. Moreover, we modularized the DRM components for easy extension and integration. For better performance on low‐end devices, parameters of encryption are introduced, namely, the key size and the encryption density. We addressed the mask shift problem caused by random access and implemented the device identifier acquirement. The DRM system also proved to have high security and good performance in our analysis. Copyright © 2017 John Wiley & Sons, Ltd.